Midwives' survey of their weight management practice before and after the GLOWING guideline implementation intervention: A pilot cluster randomised controlled trial. - Nicola Heslehurst; Catherine McParlin; Falko F Sniehotta; Judith Rankin; Elaine McColl (PLoS ONE)
Background Maternal weight management is a priority due to pregnancy risks for women and babies. Interventions significantly improve maternal diet, physical activity, weight, and pregnancy outcomes. There are complex barriers to midwives' implementation of guidelines; low self-efficacy is a core implementation barrier. The GLOWING intervention uses social cognitive theory (SCT) to address evidence-based barriers to practice. The intervention aimed to support midwives' implementation of guidelines. Methods An external rehearsal pilot cluster randomised controlled trial in four NHS Trusts (clusters) in England, UK. Clusters were randomised to intervention (where all eligible midwives received the intervention) or control (no intervention delivered) arms. A random sample of 100 midwives were invited to complete questionnaires pre- and post-intervention. UK guideline recommendations relating to midwives' practice were categorised into: 1) communication-related behaviours (including weight- and risk-communication), and 2) support/intervention-related behaviours (including diet/nutrition, physical activity, weight management, referrals/signposting). Questionnaires were developed using SCT constructs (self-efficacy, outcome expectancies, intentions, behaviours) and 7-point Likert scale, converted to a 0-100 scale. Higher scores were more positive. Descriptive statistics compared intervention and control arms, pre- and post-intervention. Results Seventy-four midwives consented and 68 returned questionnaires. Pre-intervention, self-efficacy for support/intervention-related behaviours scored lowest. In controls, there was limited difference between the pre- and post-intervention scores. Post-intervention, mean (SD) scores were consistently higher among intervention midwives than controls, particularly for support/intervention self-efficacy (71.4 (17.1) vs. 58.4 (20.1)). Mean (SD) self-efficacy was higher post-intervention than pre-intervention for all outcomes among intervention midwives, and consistently higher than controls. Mean differences pre- and post-intervention were greatest for support/intervention self-efficacy (17.92, 95% CI 7.78-28.07) and intentions (12.68, 95% CI 2.76-22.59). Self-efficacy was particularly increased for diet/nutrition and physical activity (MD 24.77, 95% CI 14.09-35.44) and weight management (18.88, 95% CI 7.88-29.88) behaviours, which showed the largest increase in scores. Conclusions This study supports the theoretical models used to develop GLOWING, where low self-efficacy was a core implementation barrier. Results suggest that GLOWING successfully targets self-efficacy, potentially with a positive impact on guideline implementation. A definitive trial is required to determine effectiveness. Trial registration ISRCTN46869894, retrospectively registered 25/05/2016, http://isrctn.com/ISRCTN46869894.